MATLAB/Simulink STUDY AND IMPLEMETATION OF FAULT IDENTIFICATION OF EHV LINES USING WAVELET TRANSFORM BASED FLC - V, Balamurali; Balachander, K. (International Journal of Psychosocial Rehabilitation, 2019)
An appropriate method for fault identification and classification on extra high voltage transmission line using discrete wavelet transform is proposed in this work. The sharp variations of the generated short circuit transient signals which are recorded at the sending end of the transmission line are adopted to identify the fault. The threshold values involve fault classification and these are done on the basis of the multi resolution analysis. A comparative study of the performance is also presented for Discrete Fourier Transform (DFT) based Fuzzy Logic Controller (FLC) and DWT. The results prove that the proposed method is an effective and efficient one in obtaining the accurate result wit.hin short duration of time. Simulation of the power system is carried out MATLAB/Simulink